2020
DOI: 10.3389/fphys.2020.570118
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tool for the Identification and Characterization of Repetitive Patterns in High-Density Contact Mapping of Atrial Fibrillation

Abstract: Introduction: Electrical contact mapping provides a detailed view of conduction patterns in the atria during atrial fibrillation (AF). Identification of repetitive wave front propagation mechanisms potentially initiating or sustaining AF might provide more insights into temporal and spatial distribution of candidate AF mechanism and identify targets for catheter ablation. We developed a novel tool based on recurrence plots to automatically identify and characterize repetitive conduction patterns in high-densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 45 publications
(49 reference statements)
3
18
0
Order By: Relevance
“…We further acknowledge that not all researchers in the field agree with the notion of phase transformation and the study of phase singularity dynamics in AF ( Podziemski et al, 2018 ). We also note that in the electrogram-based component of the current study that sinusoidal recomposition was used for phase reconstruction, and recognize that other approaches such as linear interpolation of phase between activation times in the unipolar electrogram have been suggested as important alternative approaches to phase recomposition ( Zeemering et al, 2020 ). Although this approach was not utilized in this current investigation, we would anticipate it could also potentially lead to PS dynamics that could be modeled with an M/M/infinity process, as we found that M/M/infinity approaches were effective in the optically mapped and simulated AF data where transmembrane voltage was able to be directly ascertained.…”
Section: Discussionmentioning
confidence: 89%
“…We further acknowledge that not all researchers in the field agree with the notion of phase transformation and the study of phase singularity dynamics in AF ( Podziemski et al, 2018 ). We also note that in the electrogram-based component of the current study that sinusoidal recomposition was used for phase reconstruction, and recognize that other approaches such as linear interpolation of phase between activation times in the unipolar electrogram have been suggested as important alternative approaches to phase recomposition ( Zeemering et al, 2020 ). Although this approach was not utilized in this current investigation, we would anticipate it could also potentially lead to PS dynamics that could be modeled with an M/M/infinity process, as we found that M/M/infinity approaches were effective in the optically mapped and simulated AF data where transmembrane voltage was able to be directly ascertained.…”
Section: Discussionmentioning
confidence: 89%
“…Atrial propagation patterns during atrial fibrillation (AF) can be characterize by a certain degree of recurrence [1][2][3][4][5][6], which can be associated with different types of reentrant circuits that can drive the arrhythmia. The investigation of how well this dynamic behavior of atrial activity (AA) propagation patterns during AF can be noninvasively characterized by analyzing ECG signals is relevant in order to improve AF patient stratification and treatment selection, without resorting to invasive analysis.…”
Section: Introductionmentioning
confidence: 99%
“…RBF interpolation does not require any assumptions on the spacing and/or density of the interpolation points (Fornefett et al, 2001;Kybic et al, 2002a,b). This allows integration with different clinically available mapping systems, with respect to other approaches (Rogers et al, 1997;Bayly et al, 1998;Alcaine et al, 2014;Zeemering et al, 2020) proposed in the experimental setting, which instead require regularly spaced and/or high-density latency data. In this study we demonstrated the capability of RBFs to accurately reconstruct CV fields from the analysis of simultaneous electrograms from multipolar catheters and we showed that the application of operators, such as the divergence, to the calculated CV fields could be used to identify focal drivers in the presence of complex propagation patterns.…”
Section: Radial Basis Function-based Conduction Velocity Vector Approach For the Characterization Of Propagation Patternsmentioning
confidence: 99%